2008
DOI: 10.1097/ccm.0b013e31818b8dbd
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevating the head of bed on interface pressure in volunteers

Abstract: Raising the head of bed to 30 degrees or higher on a intensive care unit bed increases the peak interface pressure between the skin at the sacral area and support surface in healthy volunteers. At 45 degrees head of bed elevation or higher, the affected area attributed to a skin-intensive care unit bed interface pressure >or=32 mm Hg increased as well. Further study is needed to determine whether the increased peak interface pressures and affected areas that result from raising the head of bed actually increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
(13 reference statements)
3
52
1
5
Order By: Relevance
“…This finding, however, is consistent with the results of Peterson et al, 19 who also observed a significantly higher number of sensor cells reading 32 mm Hg or greater at the 45° semirecumbent position and higher angles.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding, however, is consistent with the results of Peterson et al, 19 who also observed a significantly higher number of sensor cells reading 32 mm Hg or greater at the 45° semirecumbent position and higher angles.…”
Section: Discussionsupporting
confidence: 78%
“…This result differs from that of a recent investigation 19 in which peak pressures differed significantly between supine and 30° semirecumbent positions. Peterson et al 19 examined the effects of 7 different angles of backrest elevation on sacral interface pressures in healthy volunteers on a single bed used in an intensive care unit. Sacral peak pressures in the supine position were comparable to our findings, but peak pressures in the semirecumbent positions of 30° and 45° were higher.…”
Section: Discussioncontrasting
confidence: 56%
“…Adopting a supine posture with the head of the bed elevated alters loading on the buttocks, which is why it is a controversial posture. Elevating only the head of the bed increases both the normal and frictional forces on the sacrum [38][39]. Mechanics suggests that as the head elevates, more of the upper-body weight will be transmitted through the buttocks to the supporting surface.…”
Section: Positioning Devices and Posturementioning
confidence: 99%
“…19,20 Guidelines for preventing pressure ulcers recommend HOB elevation of 30º or less. 21,22 Based on these conflicting guidelines and difficulty maintaining higher HOB elevations, a study was needed to compare the outcomes of reflux, aspiration, and pressure ulcers simultaneously.…”
mentioning
confidence: 99%